Regulation of alternative mRNA splicing: old players and new perspectives - Dvinge, Heidi (FEBS letters, 2018)
Nearly all human multiexon genes are subject to alternative splicing in one or more cell types. The splicing machinery therefore has to select between multiple splice sites in a context‐dependent manner, relying on sequence features in cis‐ and trans‐acting splicing regulators that either promote or repress splice site recognition and spliceosome assembly. However, the functional coupling between multiple gene regulatory layers signifies that splicing can also be modulated by transcriptional or epigenetic characteristics. Other, less obvious, aspects of alternative splicing have come to light in recent years, often involving core components of the spliceosome previously thought to perform a basal rather than a regulatory role in splicing. Together this paints a highly dynamic picture of splicing regulation, where the final splice site choice is governed by the entire transcriptional environment of a gene and its cellular context.